2009
DOI: 10.1159/000195695
|View full text |Cite
|
Sign up to set email alerts
|

PAX6 Immunoreactivity in the Diencephalon and Midbrain of <i>Alligator</i> during Early Development

Abstract: PAX6 expression was examined during early development of the diencephalon and midbrain of Alligator using an immunocytochemical methodology. These observations focused on the basal plate to determine whether diencephalic prosomere organization in this region followed a pattern previously identified for alar plate areas. PAX6 expression was also described in alar diencephalic regions and the adjacent midbrain. PAX6 (+) cells in the basal plate were first seen in prosomere 1 at stage 7, in the midbrain at stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 73 publications
6
29
0
Order By: Relevance
“…Within p3 in all vertebrates studied, the prethalamic eminence shows ventricular Pax6 expression while the PTh is filled with Pax6 expressing cells also in the subventricular and mantle zones (Puelles et al, 2000; Wullimann and Rink, 2001, 2002; Bachy et al, 2002; Moreno et al, 2008, 2010, 2012b; Pritz and Ruan, 2009; Duan et al, 2012; Domínguez et al, 2013; present results). In the alligator, the boundary between p3 and the secondary prosencephalon was defined by Pax6 expression, and Pax6 cells were also reported in the basal part of p3 (Pritz and Ruan, 2009). In the turtle Pseudemys scripta , scattered Pax6 cells were seen to invade the basal portion of p3 (Moreno et al, 2012b).…”
Section: Discussionsupporting
confidence: 61%
“…Within p3 in all vertebrates studied, the prethalamic eminence shows ventricular Pax6 expression while the PTh is filled with Pax6 expressing cells also in the subventricular and mantle zones (Puelles et al, 2000; Wullimann and Rink, 2001, 2002; Bachy et al, 2002; Moreno et al, 2008, 2010, 2012b; Pritz and Ruan, 2009; Duan et al, 2012; Domínguez et al, 2013; present results). In the alligator, the boundary between p3 and the secondary prosencephalon was defined by Pax6 expression, and Pax6 cells were also reported in the basal part of p3 (Pritz and Ruan, 2009). In the turtle Pseudemys scripta , scattered Pax6 cells were seen to invade the basal portion of p3 (Moreno et al, 2012b).…”
Section: Discussionsupporting
confidence: 61%
“…In our study a number of regulatory genes displayed ventral expression sites that may be analytical for defining prosomeric subdivisions within the basal plate. For instance, as in other vertebrates, a separate zebrafish pax6a expression domain was identified beneath the pretectum corresponding to basal p1 (Ferran et al, 2007;Pritz and Ruan, 2009). Strong nkx6.1 and nkx6.2 expression domains extended from the midbrain tegmentum beneath the alar pretectum, thus respecting the basal p1/p2 boundary.…”
Section: Prosomeric Boundaries Within the Basal Platementioning
confidence: 86%
“…Abundant immunohistochemical studies have described distinct distributions of many neuropeptides/neurotransmitters in the reptilian hypothalamus (Fernández-Llebrez et al, 1988;Sherwood and Whittier, 1988;Inagaki et al, 1990;Jiménez et al, 1994;D'Aniello et al, 1999;Wang et al, 1999;Smeets et al, 2003;López et al, 2008;Muñoz et al, 2008;Domínguez et al, 2009) and its hodology has also been analyzed (Bruce and Neary, 1995a,b;Lanuza et al, 1997). In addition, a few studies have reported important molecular data on telencephalic (Smith-Fernández, 1998;Métin et al, 2007;Moreno et al, 2010) and diencephalic (Pritz and Ruan, 2009) specification in reptiles.…”
Section: Preliminary Considerations: Selection Of the Markers Usedmentioning
confidence: 99%
“…The homeobox gene Tbr1 was extremely useful in the recognition of the prethalamic eminence Brox et al, 2004). Pax6 and Pax7 transcription factors show conserved expression patterns in all vertebrates studied, including reptiles (Stoykova and Gruss, 1994;Smith-Fernández et al, 1998;Puelles et al, 2000;Bachy et al, 2002;Moreno et al, 2008aMoreno et al, , 2010Pritz and Ruan, 2009). In addition, the expression of Pax6 served to identify the boundaries of the diencephalic prosomeres (Moreno et al, 2008a;Ferran et al, 2009;Morona et al, 2011).…”
Section: Preliminary Considerations: Selection Of the Markers Usedmentioning
confidence: 99%
See 1 more Smart Citation